Mempromosikan Bir Pletok Sebagai Minuman Khas Betawi Melalui Penyajian sebagai Welcome Drink - Lila Muliani (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
This study aims to obtain a description of the concept of local culinary-based tourism typical of Betawi, especially Pletok Beer. As a tourism product, a series of strategies and promotions should be prepared so that traditional drinks made from healthy spice extracts are worthy of being ambassadors representing Betawi culinary riches as well as having consistent standards of taste and optimal organoleptic quality. In addition, it is also designed to make factual and accurate description and description of historical facts related to Pletok Beer as one of Betawi local wisdom. The selection of Pletok Beer producers was conducted in 5 administrative areas, namely East Jakarta, South Jakarta, West Jakarta, Central Jakarta and North Jakarta.Jakarta is a city that has many functions and roles. Status as a modern city with a massive wave of development invasion also played a role to wipe out the existence of ethnic Betawi, the native inhabitants of Jakarta who deservedly welcome the presence of the immigrants. As one of the tourist destinations in Indonesia, quite a lot of Jakarta's local culture can be developed and promoted, including culinary riches. There are a line of delicious and unique dishes that are very potent Betawi so the appeal of the culinary tourist, either because of taste, health benefits, or the value of philosophy and history that accompany it. Unfortunately until now the Betawi culinary wealth has not become a reason for tourists to come to Jakarta.The results showed that Pletok Beer as a part of Betawi culinary wealth got support and positive appreciation if presented as welcome drink. Making Concentrate Beer Pletok be one way that can facilitate the storage and presentation so that more practical and efficient. Preparation of concentrate with concentration of 1/4 times and boiling time for 60 minutes in the research scale (1/2 recipe), proven to produce Pletok Beer Concentrate with taste and aroma quality that is not different from fresh Pletok beer without concentration.